Monkey-Pox: A Silent Return - Mittal, Avi; Chauhan, Mahi; Kalwana, Mehak; Esha; Mittal, Shailesh (Disease and Health: Research Developments Vol. 3, 2025)
Monkeypox is a viral zoonotic disease caused by the monkeypox virus, part of the Orthopoxvirus genus, primarily found in Central and West Africa. Its symptoms are similar to smallpox but generally milder, including fever, lymphadenopathy, and a rash that progresses from macules to pustules. The virus spreads through direct contact with infected animals or humans, raising public health concerns, especially with recent outbreaks in non-endemic areas. There are two monkeypox clades: Central African and West African, with the former leading to more severe illness. The virus enters through broken skin or mucous membranes, spreads via the lymphatic system, and triggers an immune response crucial for infection control. Immunocompromised individuals face higher risks of complications. Recent outbreaks have seen increased human-to-human transmission, notably among specific demographics. Diagnosis involves clinical evaluation and lab tests, while treatment focuses on symptom management. Preventive strategies include vaccinations for high-risk groups, public education, enhanced surveillance, and inter-agency collaboration to control outbreaks effectively. Ongoing research and public health efforts remain essential as the situation evolves.